Cynicism and the Collapse of Multilateralism - Mahbi Maulaya (President University, 2020)
International order is now witnessing the declining efficacy and extremely fragile condition of multilateralism. Several states start to doubt and leave international treaties, agreements, organizations, and institutions. This circumstance led into the speculation of “Multilateralism Collapse